Recruitment of Polymorphonuclear Myeloid-Derived Suppressor Cells During Cryptococcus neoformans Infection - JOYCE C. GUIMARÃES-DE-OLIVEIRA; ISRAEL DINIZ-LIMA; IDÁLIA M. FERREIRA-DOS-SANTOS; ELIAS B. DA SILVA-JUNIOR; LUCIANA P. COVRE; MATHEUS FREIRE-DE-LIMA; LEONARDO M. DA FONSECA; ALEXANDRE MORROT; LEONARDO FREIRE-DE-LIMA; LUCIA MENDONÇA-PREVIATO; JOSE O. PREVIATO; HERBERT L. DE MATOS GUEDES; et al. (Anais da Academia Brasileira de Ciências)
Abstract Cryptococcosis is a disease originating in the lungs, often seen in immunosuppressed patients. In severe cases, it can lead to meningoencephalitis and can be fatal. Biochemical studies have shown that the capsule of Cryptococcus neoformans is predominantly composed of glucuronoxylomannan (GXM), with glucuronoxylomannogalactan (GXMGal) present in smaller amounts. These polysaccharides have different effects on the immune system, with GXM mainly having anti-inflammatory properties, while GXMGal is more pro-inflammatory. Myeloid-derived suppressor cells (MDSCs) are a diverse group of immature myeloid cells, including progenitor cells and precursors of macrophages, granulocytes, and dendritic cells at different stages of development. MDSCs are known to suppress immune responses in various diseases, including bacterial and fungal infections, through mechanisms such as the inhibition of T cell proliferation. In this study, we show that infection with either B3501 or CAP67 strains results in the accumulation of granulocytic MDSC precursors in bronchoalveolar cavities. The MDSCs recruited by the B3501 strain suppress T cell proliferation, while those recruited by the CAP67 strain do not. Furthermore, we observed the expression of PD-L1 on these MDSCs, suggesting a potential mechanism of immunosuppression during infection. These findings reveal how the polysaccharides of C. neoformans might weaken the host’s immune defense.